A política de recompensa e sua influência na motivação do trabalhador - Pinho, Marcio Gonçalves de (2015)
This research addresses the reward policy of a company, understood here as the policy that comprises joins monetary compensation and the promotion system, and its influence on the employee’s motivation. The research aims to identify – among the perceived characteristics of the policy reward transparency of rules, fairness in its application and in decisions, laborer’s controllability on his trajectory in the company – which ones impact on motivation? The literature distinguishes the intrinsic motivation, understood as the individual's own stimuli, and extrinsic, this one tending to be sensitive to the company’s actions. So, in this study we seek to observe the level of motivation according to these two concepts, which are the explained variables of our model. The theoretical framework includes Herpen (2007), as well as Mitchell et al. (2001), Vieira and Silva (2008) and Nars, Ferreira and Fischer (2013), empirical studies that often present contradictory results on the theme and are generally focused on large companies. This work seeks to enrich this line of research by means of a case study involving a medium-sized family pharmaceutical industry of Rio de Janeiro. Data were collected through a semi-structured questionnaire and examined through factor analysis and multiple regression. The results show that the justice in monetary compensation has relevant positive and statistically significant influence, both on extrinsic and intrinsic motivation. The results also show that the controllability of the promotion system has a positive influence on extrinsic motivation, while the transparency of monetary compensation revealed a negative influence on intrinsic motivation. Among the control variables used in the model, the statistics revealed that workers with Age under 35 tend to have lower extrinsic motivation and workers over 44 tend to have higher intrinsic motivation. We also found a significant and positive relationship between intrinsic motivation and female workers and/or those engaged in management positions, but workers of the administrative and packaging sectors tend to lower intrinsic motivation.